P-009 EmboTrap extraction and clot evaluation and lesion evaluation for neurothrombectomy: methods for the EXCELLENT registry. (22nd July 2019) - Siddiqui, A; Andersson, T; De Meyer, S; Doyle, K; Fiehler, J; Hacke, W; Hanel, R; Jovin, T; Kallmes, D; Liebeskind, D; Yoo, A; Zaidat, O; et al.
Abstract : Rationale: The EmboTrap Revascularization Device has been shown to be effective in achieving successful reperfusion in emergent large vessel occlusion (ELVO) patients, with clinical outcomes comparable to existing stent retriever devices. Prospective multicenter data on the real-world experience with EmboTrap is not available. Aim: The primary objective of the study is to assess the efficacy of routine, real-world experience of the EmboTrap and to explore the associations between imaging characteristics at presentation, including volume of core and penumbra, final infarct volume, histologic clot characteristics, subject comorbidities, revascularization rate, and clinical outcomes. Design: This is a prospective, global, multi-center, single-arm, observational registry. Up to 1000 subjects at 50 different sites in Europe and US may be enrolled in the study. Adult patients (>18 years) with angiographically confirmed ELVO, and treated with EmboTrap as first attempted device will be eligible for participation in the study. Patients with confirmed pregnancy or enrolled in another investigational clinical trial will be excluded. This study will utilize expanded thrombolysis in cerebral infarction score (eTICI) and an independent Core Imaging Laboratory to assess baseline CT/MR imaging (e.g. ASPECTS, infarct volume, clot location, perfusion), procedural angiography (eTICI score for every pass, emboli to new territories, collateral score) and post-procedure CT/MR imaging (infarct volume, intracranial hemorrhage). All imaging will be read independently by an experienced Imaging Core Lab blinded to all clinical data. In addition, an independent Core Laboratory will also perform clot analysis. Study outcomes: Pre-specified endpoints of the study include successful revascularization (modified thrombolysis in cerebral infarction score ≥ 2b), first pass effect (eTICI ≥ 2c in a single pass without rescue), number of passes, functional independence assessed as modified Rankin Score of ≤ 2 at 90 days, 2 rates of embolization to new territory, symptomatic intracranial hemorrhage at 24 hours and all-cause mortality at 90 days. Analysis: Standard descriptive statistical summaries will be provided. For categorical endpoints, two-sided exact 95% confidence intervals will be presented. Regression analyses will be conducted to determine the association between baseline subject comorbidities, clot characteristics and reperfusion, with a focus on imaging findings. The plan for per pass analysis both by an independent core imaging laboratory and by an independent clot analysis laboratory sets apart this registry from other similar studies. In addition, the reperfusion assessment by the independent core lab will be using innovative eTICI. Disclosures: A. Siddiqui: 1; C; Co-investigator NIH/NINDS 1R01NS091075. 2; C; Amnis Therapeutics, Boston Scientific, Canon Medical Systems USA Inc, Cerebrotech Medical Systems, Cerenovus, Corindus Inc., Endostream Medical Ltd, Guidepoint Global Consulting, Imperative Care, Integra LifeSciences Corp, Medtronic, MicroVention, Q'Apel Medical Inc, Rapid Medical, Rebound Therapeutics Corp., Serenity Medical Inc, Silk Road Medical, StimMed, Stryker, Three Rivers Medical, VasSol, W.L. Gore & Associates. 4; C; Amnis Therapeutics, Apama Medical, Blink TBI Inc, Buffalo Technology Partners Inc, Cardinal Consultants, Cerebrotech Medical Systems, Cognition Medical, Endostream Medical Ltd, Imperative Care, International Medical Distribution Partners, Neurovascular Diagnostics Inc, Q'Apel Medical Inc, Rebound Therapeutics Corp, Rist Neurovascular In, Serenity Medical, Silk Road Medical, StimMed, Synchron, Three Rivers Medical Inc, Viseon Spine. T. Andersson: 2; C; Neuravi, Ablynx, Amnis Therapeutics, Medtronic, Rapid Medical, Stryker. S. De Meyer: None. K. Doyle: None. J. Fiehler: None. W. Hacke: None. R. Hanel: 2; C; Three Rivers Medical, Medtronic, Microvention, Codman, Stryker. T. Jovin: 2; C; Neuravi, codman, Medtronic, Stryker, Silk Road, Anaconda, Blockade Medical. D. Kallmes: None. D. Liebeskind: None. A. Yoo: 2; C; Cerenovus. O. Zaidat: 2; C; Stryker, Medtronic, Neuravi, Penumbra. R. Nogueria: 2; C; Neuravi, Medtronic, Penumbra, Stryker.